Isu-isu Terkini dalam Teologi Reformed Injili - Foord, Martin (STT Reformed Injili Internasional, 2024)
Reformed theology rightly is drawn not just from Scriptural statements but also “what may be truly and certainly proved” from them. But what is the status of proofs (or logical consequences) from Scripture? And how many “consequences” can we take beyond Scripture before they become speculative and are no longer “good” or “necessary”? Reformed and Evangelical theology needs to explore a clearer understanding and formulation of what precisely constitute “good and necessary consequences” of Scripture.